An Investigation of The J-V Curve for N-AlGaAs/p-GaAs Heterojunction Solar Cell Due to Influence of Surface Recombination Velocity (Journal of Pure & Applied Sciences, 2023)
Theoretical analysis can substantially reduce the time and costs required for developing a specific device such as solar cell, by allowing the designer to take a suitable geometry and doping profile prior to the fabrication stage. In this paper, theoretical analysis of electric field and electric potential within depletion layer of N-AlGaAS/p-GaAs has been made by solving Poisson's equation numerically using finite difference method (FDM) with Fortran program. Continuity equations of charge carriers in quasi- nature regions in N and p-layers  were solved numerically to obtain the current density curve (J-V curve). Boundary conditions related to surface recombination velocity were implemented in this analysis. The effect of front and back surface recombination velocity on the excess minority carriers distribution and photocurrent have been studied. The aim of this work is to find the influence of surface recombination velocity in the output of N-AlGaAs/p-GaAs heterojunction solar cell. The analysis showed that, the low surface recombination velocity produce high efficient solar cell.